Planning and Evaluation of Bioequivalence Studies of Telmisartan Generic Drug Products - A. L. Khokhlov; D. P. Romodanovsky; A. E. Miroshnikov (Разработка и регистрация лекарственных средств, 2019)
Introduction. Telmisartan is a modern antihypertensive drug, from the group of angiotensin II receptor antagonists, which, recently, has been the purpose of the development and registration of generic drug. The pharmaceutical development of telmisartan generics and their evaluation in bioequivalence studies is complicated by many factors that influence the results of comparison with the reference drug. Therefore, it is relevant to study these factors for the proper planning of studies and for evaluating their results from the generic drugs of telmisartan.Aim. The aim of the study is to identify the key factors that should be considered in planning and evaluation of bioequivalence studies of telmisartan’s generics.Materials and methods. To identify the key factors influencing the planning and evaluation of studies of telmisartan generics, a retrospective analysis of the results of seven telmisartan studies was conducted. Calculated pharmacokinetic parameters Cmax, AUC0-t, tmax; their average values; the values of intraindividual variability for each study and the average of the coefficients of intraindividual variability obtained.Results and discussion. The results of the study demonstrated that the drugs of telmisartan are highly variable, there are sex differences in the pharmacokinetics of telmisartan. According to the averaged values of the concentrations and pharmacokinetic profiles of telmisartan, the following areas were determined: the area of maximum exposure of telmisartan, the duration and schedule of blood sampling, to obtain the optimal pharmacokinetic profile. The most optimal method for the determination of telmisartan is HPLC MS/MS with a lower limit of quantification in the range of 0.5–3 ng/ml. The upper limit of the 90% confidence interval was calculated for the pooled average of the coefficients of intraindividual variability obtained in the considered studies.Conclusion. Recommendations were developed for planning and evaluating bioequivalence studies of generic telmisartan preparations. It is necessary to plan bioequivalence studies with replicated design in three or four periods, with two crossovers, with two sequences of drug intake. To assess the pharmacokinetics of telmisartan one should use the data on its exposure given in the article. When determining the sample size, one should be guided by the upper limit of the confidence interval of the averaged values of the coefficient of intra-individual variability Cmax  of telmisartan (45%). Evaluation of results should be carried out taking into account the possibility of scaling bioequivalence limits for the Cmax. The bioequivalence limit for the AUC0-t  parameter should remain in the range of 80.00–125.00%, as well as the ratio of geometric means for both parameters.